2011
DOI: 10.1371/journal.pone.0026203
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Characterization of the FMR1 Gene and Aberrant Neurodevelopment in Human Induced Pluripotent Stem Cell Models of Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is the most common inherited cause of intellectual disability. In addition to cognitive deficits, FXS patients exhibit hyperactivity, attention deficits, social difficulties, anxiety, and other autistic-like behaviors. FXS is caused by an expanded CGG trinucleotide repeat in the 5′ untranslated region of the Fragile X Mental Retardation (FMR1) gene leading to epigenetic silencing and loss of expression of the Fragile X Mental Retardation protein (FMRP). Despite the known relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
274
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(290 citation statements)
references
References 43 publications
11
274
2
3
Order By: Relevance
“…We previously reported on the aberrant patterns of expression for SOX1, NOTCH1, and PAX6 during IVND of FX-hESCs and reduced neuronal yields compared to controls [17]; in this study, we provide data suggesting a role for SOX2 and SOX9, and excluding a role for GSK3b. Using FX-hiPSCs, others have found a significant reduction in SOX1 expression and a similar phenotype of reduced neuronal yields [18], suggesting that these phenotypes are strongly correlated with a reduction in FMR1 expression in both models. Finally, a recent study using FX-hiPSCs suggested a role for the transcription repressor REST in FXS neuropathology [19], but these results have not yet been tested in any other model.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We previously reported on the aberrant patterns of expression for SOX1, NOTCH1, and PAX6 during IVND of FX-hESCs and reduced neuronal yields compared to controls [17]; in this study, we provide data suggesting a role for SOX2 and SOX9, and excluding a role for GSK3b. Using FX-hiPSCs, others have found a significant reduction in SOX1 expression and a similar phenotype of reduced neuronal yields [18], suggesting that these phenotypes are strongly correlated with a reduction in FMR1 expression in both models. Finally, a recent study using FX-hiPSCs suggested a role for the transcription repressor REST in FXS neuropathology [19], but these results have not yet been tested in any other model.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, others found abnormal expression of neural genes in human neural precursor cells (hNPCs) harvested from FXS fetuses [10] and in hNPCs differentiated from FX-human-induced pluripotent stem cells (hiPSCs) generated from fibroblasts of FXS patients [18,19]. However, the functional consequences of these findings and the exact molecular mechanism regulating abnormal human neurogenesis in FXS remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances in the use of iPSCs derived from human cells enable the testing of therapeutic strategies Bin a dish^ [225]. Early studies in FXS patient-derived iPSCs suggest that some FXS-associated defects are replicated in these cells [226][227][228], although the classic phenotypes reported in the mouse model, for example exaggerated protein synthesis and altered dendritic spine morphology, have yet to be examined in FXS iPSC-derived neurons. In the future, it will be important to identify robust phenotypes in human iPSCderived neurons from FXS that are suitable to test or screen for therapeutic drugs.…”
Section: Challenges and Future Outlook For Preclinical Studiesmentioning
confidence: 99%
“…Conversely, the FMR1 gene was expressed in embryonic stem cells (ESC) from a human FXS embryo, and underwent transcriptional silencing after ESC differentiation [Eiges et al, 2007]. Recently Sheridan et al [2011] observed morphological differences in iPS-derived neurons, with FXS cells having fewer and shorter neurites than controls, like in Fmr1 knockout mice [Huber et al, 2002] and in human postmortem brains [Irwin et al, 2000]. Neuronal cells are crucial to investigate the effect of drugs acting on either the epigenetic status of FMR1 (5-azadC) or downstream pharmacological targets, like the mGluR pathway.…”
Section: Fragile X Syndromementioning
confidence: 99%